Дзеркальна симетрiя як основа побудови просторово-часового континууму - Khoroshkov, Yu. V. (Publishing house "Academperiodika", 2019)
By mirroring a one-dimensional oriented set in a complex space specially created on the basis of a symmetry, a mirror n-dimensional space with n > 1 has been constructed. The geometry of the resulting space is described by the Clifford algebra. On the basis of the algebra of hyperbolic hypercomplex numbers, a pseudo-Euclidean space has been constructed with the metric of the Minkowski space. The conditions for a function of a hyperbolic hypercomplex argument to be analytic (h-analyticity) are obtained. The conditions implicitly contain the Maxwell equations for the 4-potential in a free space.